CXCR4 antagonists disrupt leukaemia‐meningeal cell adhesion and attenuate chemoresistance. (19th December 2022) - Jonart, Leslie M.; Ostergaard, Jason; Brooks, Athena; Fitzpatrick, Garrett; Chen, Liam; Gordon, Peter M.
Summary: The effective prophylaxis and treatment of central nervous system (CNS) involvement in acute lymphoblastic leukaemia (ALL) remains a significant clinical challenge. Developing novel and more effective CNS‐directed therapies has been hampered, in part, by our limited understanding of the leukaemia niche in the CNS relative to the bone marrow. Accordingly, defining the molecular and cellular components critical for the establishment and maintenance of the CNS leukaemia niche may lead to new therapeutic opportunities. In prior work we showed that direct intercellular interactions between leukaemia and meningeal cells enhance leukaemia chemoresistance in the CNS. Herein, we show that the CXCR4/CXCL12 chemokine axis contributes to leukaemia‐meningeal cell adhesion. Importantly, clinically tested CXCR4 antagonists, which are likely to cross the blood–brain and blood‐cerebral spinal fluid barriers and penetrate the CNS, effectively disrupted leukaemia‐meningeal cell adhesion. Moreover, by disrupting these intercellular interactions, CXCR4 antagonists attenuated leukaemia chemoresistance in leukaemia‐meningeal cell co‐culture experiments and enhanced the efficacy of cytarabine in targeting leukaemia cells in the meninges in vivo. This work identifies the CXCR4/CXCL12 axis as an important regulator of intercellular interactions within the CNS leukaemia niche and supports further testing of the therapeutic efficacy of CXCR4 antagonists in overcoming CNS niche‐mediated chemoresistance.